2011
DOI: 10.1016/j.gca.2010.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry of hydrothermal fluids from the PACMANUS, Northeast Pual and Vienna Woods hydrothermal fields, Manus Basin, Papua New Guinea

Abstract: Processes controlling the composition of seafloor hydrothermal fluids in silicic back-arc or neararc crustal settings remain poorly constrained despite growing evidence for extensive magmatichydrothermal activity in such environments. We conducted a survey of vent fluid compositions from two contrasting sites in the Manus back-arc basin, Papua New Guinea, to examine the influence of variations in host rock composition and magmatic inputs (both a function of arc proximity) on hydrothermal fluid chemistry. Fluid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
190
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 184 publications
(198 citation statements)
references
References 175 publications
7
190
0
1
Order By: Relevance
“…5a). It has been suggested that higher than seawater Mg in hydrothermal fluids may possibly occur as a result of acid leaching of Mg from host rocks in arc/back-arc systems where the pH is exceedingly low (Gamo et al, 1997;Reeves et al, 2011;Resing et al, 2007). We hypothesize that acid alteration is causing the Mg enrichments in Panarea fluids.…”
Section: Secondary Processesmentioning
confidence: 77%
See 3 more Smart Citations
“…5a). It has been suggested that higher than seawater Mg in hydrothermal fluids may possibly occur as a result of acid leaching of Mg from host rocks in arc/back-arc systems where the pH is exceedingly low (Gamo et al, 1997;Reeves et al, 2011;Resing et al, 2007). We hypothesize that acid alteration is causing the Mg enrichments in Panarea fluids.…”
Section: Secondary Processesmentioning
confidence: 77%
“…The final compositions are a function of many factors including fluid-mineral equilibrium, phase separation, magmatic inputs, mineral precipitation, and mixing. While these processes have been well defined for deep-sea systems along mid-ocean ridges, and more recently at back-arc basins (Reeves et al, 2011), much less is known about the subsurface processes taking place at shallow-sea hydrothermal vents. They are most often associated with island arc volcanoes, and thus silicic magmas more similar to back-arc basins rather than mid-ocean ridges.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…Fluid aliquots were transferred into sealed glass tubes fitted with Teflon and stainless steel valves for shore-based C 2 H 6 and C 3 H 8 analysis using a purge and trap device interfaced to molecular-sieve GC with flame ionization detection (34). Dissolved Cl and ΣHCOOH abundances were determined by ion chromatography (36,37). Dissolved Mg concentrations were determined on a ThermoElectron Element2 inductively coupled plasma mass spectrometer (MS) (36,38).…”
Section: Methodsmentioning
confidence: 99%